Opinions of Pupils of Lower Grades of Primary School Regarding Leisure Time and Spending Time in Nature - Dragan S. Branković; Dragan D. Martinović; Vladimir K. Miletić; Željko M. Rajković (University of Belgrade, Teacher Education Faculty, 2018)
This survey was conducted to determine how children spend their free time, the frequency of spending time outdoors, as well as the attitudes of children toward outdoor activities and spending several days in the nature in the form of camping. By using the method of experimental research, the techniques of theoretical analysis and a specially designed questionnaire, we obtained the results for the analysis and consideration. What is alarming is the fact that even 20% of the children in the lower grades of primary school spend their free time in front of televisions and with computers, while as many as 45% of children rarely spend time in nature. The three most frequently cited reasons for not spending enough time in nature include school obligations, parents' obligations and the fact that there is no nature in the respondents' environment. The data indicate the need for an organised, systematic stay in the countryside at weekends in the form of half-day or full-day trips and excursions, as well as multi-day camping trips organised during summer holidays. The willingness of as many as 84.9% of the respondents to spend their free time camping meets one of the most important requirements for a systemic implementation of this programme. The children are aware of the value of spending time in nature and they feel the need and desire to spend their free time outdoors, which reflects the practical significance of this study.